ATTITUDE WORK AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Juwita Juwita; Tjutju Yuniarsih; Rofi Rofaida (Green Publisher, 2023)
Behavior we're in place work often depend on feelings We moment be there. With method this, understand how individual Act depend on understanding perspective profession them. A attitude touch on conclusions, beliefs and sentiments We about part from condition us. we have mentality to our food eat, people we invite get along, the course we are take, and other things. on the spot work, two mentality profession certain have potency best for affect method We act. This is fulfillment work and responsibilities answer authoritative. Fulfillment profession refers to the emotions you have individual to activity them. If quantity satisfaction-directed studies work Becomes marker, satisfaction work possible is mentality the most significant activity. Not quite enough answer authoritative is connection the enthusiasm you have individual to association the place they work. There is serious coverage Among fulfillment jobs and assignments authoritative, because satisfying stuff We with activity We often make we are also getting dedicated to the organization. Organization accept that perspective this proper for followed because they in a manner regular connected with significant outcomes, for example, execution, helping others, truancy and commutation